Changes in pathogenesis-related gene expression in response to bioformulations in the apoplast of maize leaves against Fusarium oxysporum. Issue 1 (1st January 2019) - Butt, Usmara Riaz; Naz, Rabia; Nosheen, Asia; Yasmin, Humaira; Keyani, Rumana; Hussain, Ishtiaq; Hassan, Muhammad Nadeem
ABSTRACT: In present study, we initially tested four different plant species Aristolochia indica (leaf), Cuscuta pedicellata (stem), Melilotus indicus (leaf) and Tribulus terresteris (leaf and fruit) for their antifungal potential against F. oxysporum. Among the studied plant species, T. terresteris (fruit) and C. pedicellate showed the maximum antifungal potential by 92% and 89%, respectively. We then investigated the potential of CHI, MeJA, and plant extracts ( C. pedicellate and T. terristris ) alone as well as in combinations in pot experiment. Treatments with the extracts of C. pedicellata and T. terresteris in combination with MeJA resulted in decrease in disease severity by 93% and 89%, respectively, and enhanced the plant growth. We observed significant elevated levels of expression of pathogenesis-related (PR-1) proteins (β-1-3-glucanase, chitinase, phenyl-alanine ammonia lyase (PAL), lipoxygenase, lipid transfer protein and PR protein) and defense enzymes (β-1-3-glucanase, chitinase, peroxidase, polyphenoloxidase and PAL) in the CHI and MeJA in combination with plant extracts-treated plants for defense signaling pathways in the apoplast of maize leaves compared to the inoculated control. We found CHI in combination with C. pedicellata most effectively induced the plant defense mechanisms against F. oxysporum through increased induction in the level of expression of PR-proteins. GRAPHICAL ABSTRACT: UF0001